3D scapulothoracic and isokinetic shoulder evaluation during internal/external rotation at 90° abduction in elite volleyball athletes with and without nervus suprascapularis lesion - Baeyens, J. P.; Viroux, P.; Cabri, J.; Meeusen, R. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The incidence of a n.suprascapularis lesion (NSL) in elite volleybal athletes is about 20% with a predilection at the spinoglenoid notch (Ferretti et al. 1998). Clinically presenting with a hypotrophy of the infraspinatus, these volleybal players do not complain of functional impairment nor pain. Compared to asymptomatic elite volleybal athletes, the dominant as well as the non dominant shoulder of elite volleybal athletes with NSL present increased passive external rotation in 90° abduction, and no differences for internal rotation at 90° abduction (Witvrouw et al. 2000). In elite volleybal players with NSL, isokinetic concentric mean peak torque at 60° and 180°/sec was different from the asymptomatic volleybal athletes for internal rotation in both the dominant and non dominant shoulder, but only different for external rotation in the non dominant shoulder (Witvrouw et al. 2000). No study combined isokinetic strength measurement with registration of dynamic scapulothoracic motion. Methods: In this study, scapulothoracic motion and isokinetic concentric strength was evaluated for external rotation/internal rotation at 90° of abduction in 6 elite volleyball athletes with NSL and 8 without (age-matched groups, 24,2+2.1yrs). Concentric isokinetic testing of 5 at 60° and 240°/sec was evaluated with the Biodex System 3 Pro, simultaneously following the 3D scapulothoracic arthrokinematics by means of electromagnetic tracking (extended Flock of Birds, Ascension Technology) which is validly applicable up to 120° of elevation. Statistic testing was done non parametrically. Parameters evaluated with Biodex included average peak torque, internal and external rotation range of motion, agonist/atagonist ratio. Results: No significant differences (.05 level) in isokinetic strenght were found in the dominant and non dominant shoulders between the NSL group and the asymptomatic group. Furthermore, in both groups, no differences in isokinetic strenght were found in between the dominant and non dominant shoulder. For the scapulothoracic motion behaviour, no significant differences were found in the scapulothoracic Euler angles between the asymptomatic control group and NSL group. Conclusion: Examining isokinetic strength and scapulothoracic motion during internal/external rotation at 90° abduction, our data show no differences in isokinetic strength and scapulothoracic motion behaviour. As such, our data differ with Witvrouw et al.`s findings (2000) This may be due to differences in patient group and measurement procedure. Anyhow, our data apply more to the reality that elite volleyball players with NSL do not complain of functional impairment.